Investigating energy and environmental issues of agro-biogas derived energy systems: A comprehensive review of Life Cycle Assessments. (June 2019) - Ingrao, Carlo; Bacenetti, Jacopo; Adamczyk, Janusz; Ferrante, Valentina; Messineo, Antonio; Huisingh, Donald
Abstract: This literature review was built upon recently published articles on Life Cycle Assessments (LCAs) of agricultural biogas plants, to: enhance understanding of the relevant literature in the field and the related question by readers worldwide. It was designed to highlight methodological issues and impact indicators, which best represent this research field; consequently, they should be considered in performing environmental assessments of agro-biogas derived energy systems. The literature review highlighted the wide variability of environmental results due to the ways the feedstock mixtures were produced, managed, and supplied; and due to the regions in which the anaerobic digesters were located and operated. Differences were found to be related to the aim and function of the study and to the methodological approach used, especially for the development of the environmental impact assessments. Other differences resulted from the ways the energy produced was utilised, whether it was used as an input to the natural gas national grid, and/or if it was used within the production system. The authors of this review concluded that, although much progress has been made, many unsolved challenges and methodological choices must be addressed to further improve the robustness of LCA in relation to AD and to related approaches. Highlights: The study reports upon results from a comprehensive literature review. The field investigated is that of biogas derived energy. Just papers dealing with Life Cycle Assessments were reviewed. Attention was focussed upon 100-year global warming potential. The review highlighted wide variability in the results.